PERAN PEMERINTAH DESA DALAM MENINGKATKAN PENDAPATAN ASLI DESA (PADESA) DI DESA PANNYANGKALANG KECAMATAN BAJENG KABUPATEN GOWA - Kaharuddin Kaharuddin; Abdul Kadir Adys; Mappigau Samma (Department of Government Studies Universitas Muhammadiyah Makassar, 2013)
Pannyangkalang Village is one of villages in the district of Bajeng in Gowa regency who have one source of income gravel mining village. Researcher aims to look at the role of government in improving revenue villages and factors supporting and inhibiting increased revenue villages, the village Pannyangkalang Bajeng district. research used in this research is descriptive. Sampling village officials concerned. The study used a technique that is purely qualitative analysis to determine the general description of the role of village government in improving village revenue (PADesa). This study used data collection techniques the researchers used the interview (interview). The results showed that the original source of rural income in the form of rural enterprises where there is no village finances are still dependent on government. While the factors supporting increased revenue villages namely the resources or the potential available and sufficient village while limiting factor in increasing revenue villages namely the rural less solid due to disagreements, lack of firmness of the village government to make policy, financial administration that has not been well , village infrastructure incomplete, resource capacity of the village officials are not qualified Pannyangkalang Village is one of villages in the district of Bajeng in Gowa regency who have one source of income gravel mining village. Researcher aims to look at the role of government in improving revenue villages and factors supporting and inhibiting increased revenue villages, the village Pannyangkalang Bajeng district. research used in this research is descriptive. Sampling village officials concerned. The study used a technique that is purely qualitative analysis to determine the general description of the role of village government in improving village revenue (PADesa). This study used data collection techniques the researchers used the interview (interview). The results showed that the original source of rural income in the form of rural enterprises where there is no village finances are still dependent on government. While the factors supporting increased revenue villages namely the resources or the potential available and sufficient village while limiting factor in increasing revenue villages namely the rural less solid due to disagreements, lack of firmness of the village government to make policy, financial administration that has not been well , village infrastructure incomplete, resource capacity of the village officials are not qualified